Potensi Terapi Sel Punca untuk Penyakit Alzheimer: Kenyataan atau Harapan? - Purba, Jan Sudir (Cermin Dunia Kedokteran, 2020)
Penyakit Alzheimer (AD) adalah penyakit neurodegeneratif menyangkut penurunan kemampuan fungsi otak yang menyebabkan gangguan perilaku serta kognitif yang progresif. Gangguan visuospasial juga sering ditemukan. Faktor risiko terbesar yang diketahui adalah bertambahnya usia dengan mayoritas 65 tahun ke atas. Perkembangan ilmu kedokteran akhir-akhir ini memungkinkan terapi sel punca pada penyakit neurodegenetatif. Dalam tulisan ini dibahas kemungkinan terapi sel punca pada penyakit Alzheimer.Alzheimer disease (AD) is a long-term and progressive neurodegenerative disorder that leads to a disability of performing simple daily tasks, often accompanied by visual disturbances. Symptoms are progressively deteriorates with age. Current therapies only target the relief of symptoms using psychotherapy and various drugs, and do not cure the disease. Stem cell therapy holds a great promise and provides a great research opportunity. Recently, stem cell therapy has been shown to be a potential approach to various diseases, including neurodegenerative disorders. In this review, we focus on stem cell therapies for AD